2017
DOI: 10.1590/s1984-29612017004
|View full text |Cite
|
Sign up to set email alerts
|

Dioctophyme renale: prevalence and risk factors of parasitism in dogs of São Cristóvão district, Três Barras county, Santa Catarina State, Brazil

Abstract: Dioctophyme renale is a nematode that can be found parasitizing the kidney, peritoneal cavity and, rarely, other organs of canids and mustelids. This disease has high occurrence in the municipality of Três Barras, state of Santa Catarina, thus making this an interesting area to study the epidemiological aspects of infection by D. renale in dogs. Among 197 dogs, 14.2% showed the parasite eggs in urine and 16.4% showed IgG antibodies anti-D. renale in serum samples according to the indirect ELISA method; among s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 17 publications
0
14
1
4
Order By: Relevance
“…In contrast to the findings of Pedrassani et al (2017) in the present work no statistically significant association of this parasitosis with sex of the dogs was observed -even though a greater number of females had been infected. Moreover, other authors have indicated a greater prevalence of dioctophymosis in males (Mace and Anderson, 1975;Colpo et al, 2007).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the findings of Pedrassani et al (2017) in the present work no statistically significant association of this parasitosis with sex of the dogs was observed -even though a greater number of females had been infected. Moreover, other authors have indicated a greater prevalence of dioctophymosis in males (Mace and Anderson, 1975;Colpo et al, 2007).…”
Section: Discussioncontrasting
confidence: 99%
“…Moriena and Ferri (1989) Coppo and Brem (1983), in a study of necropsied canines, found no case among 64 dogs in Corrientes and 7.9% among 38 assayed in Resistencia. Several authors mention similar cases in Brazil (Pedrassani and Camargo, 2004;Camargo et al, 2005;Pereira et al, 2006;Colpo et al, 2007;Pedrassani, 2009;Pedrassani et al, 2017).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The majority of reported cases come from the cold temperate regions where freshwater is available, as its life cycle requires an aquatic environment. Brazil is the country with the highest number of reported D. renale cases in domestic dogs with prevalence rates up to 14.2% (Ferreira et al, 2010;Nakagawa et al, 2007;Pedrassani et al, 2017;Rappeti et al, 2017). Canine dioctophymatosis has also been reported recently in other Latin America countries, such as Colombia (Florez et al, 2018) and Argentina (Radman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In each of the above-mentioned scenarios, the definitive host becomes infected by ingesting the fourth-(infective) stage larvae. Inside the definitive host, the Dioctophyma larva penetrates the intestinal or duodenal mucosa, enters the peritoneal cavity and migrates to the kidney, where it develops and matures into the adult form (Bowman, 2014;Pedrassani et al, 2017). Adults are able to live up to 3 years in the definitive host and the fertilized eggs that are shed into the environment may survive for up to 5 years (Radman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%